Can restaurants achieve customer retention through CSR? - Mohammedsadegh Omidvar; Anisah Deen (Journal of Applied Sciences in Travel and Hospitality, 2024)
The objective of this study is to establish a comprehensive framework that combines the four dimensions of Corporate Social Responsibility (CSR) (Economic, Legal, Ethical, and Philanthropic Responsibility) with Environmental Responsibility. Additionally, the study seeks to assess the role of Corporate Image (CI) in mediating the impact of aspects of CSR on Customer Retention with the use of structural equation modeling (SEM) to test the hypothesized conceptual framework. A total of 217 questionnaires were successfully gathered through an online platform from customers who patronized restaurants in the city of Tehran. The findings indicate that the legal, ethical, philanthropic, and environmental components have a favorable and considerable impact on CI. Moreover, the impact of the five dimensions of CSR on customer retention is mediated by the perception of the CI. This study provides a valuable contribution by expanding upon Carroll's dimensions that included environmental responsibility, and demonstrating that the inclusion of this factor can also enhance company image. Going forward managers may acquire the knowledge that enhances their environmental responsibilities can concurrently contribute to the enhancement of CI and positively impact customer retention.